PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PROBLEM BASED LEARNING DENGAN PERMAINAN PLUCKING STAR UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS IX SMP N 1 PATUK GUNUNGKIDUL - SIWI KHOMSIATUN (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2022)
This study aims to improve learning motivation and mathematical problem solving abilities of class IX students of SMPN 1 Patuk Gunungkidul in 2018 on the material of sequences and series of numbers and their use in problem solving. This research is a Classroom Action Research by adopting the model from Kemmis and Tagart which consists of several stages, namely: 1) planning, 2) action, 3) observation, and 4) reflection. The research subjects were students of class IXB SMP N 1 Patuk with 27 students. The data collection instrument used was a learning motivation questionnaire, a problem-solving ability test, and a model effectiveness questionnaire. The results of this Classroom Action Research show that the Problem Based Learning Model and the Plucking Star game can increase students' motivation to learn mathematics from an average score of 4.34 in the "very high" category in the first cycle to an average score of 4.44 in the "very high" category in the second cycle. . Problem Based Learning models and Plucking Star games can improve students' mathematical problem solving skills from an average of 84.7 with classical completeness 81.5% in the first cycle to 88.9 with 85.2% classical completeness in the second cycle. ABSTRAKPenelitian ini bertujuan untuk meningkatkan motivasi belajar dan kemampuan pemecahan masalah matematika siswa kelas IX SMPN 1 Patuk Gunungkidul tahun 2018 pada materi barisan dan deret bilangan serta penggunaannya dalam pemecahan masalah. Penelitian ini merupakan Penelitian Tindakan Kelas dengan mengadopsi model dari Kemmis dan Tagart yang terdiri dari beberapa tahap yaitu: 1) perencanaan, 2) tindakan, 3) pengamatan, dan 4) refleksi. Subjek penelitian adalah siswa kelas IXB SMP N 1 Patuk dengan 27 siswa. Instrumen pengumpulan data yang digunakan adalah angket motivasi belajar, tes kemampuan pemecahan masalah, dan angket efektifitas model. Hasil Penelitian Tindakan Kelas ini menunjukkan Model Problem Based Learning dan permainan Plucking Star dapat meningkatkan motivasi belajar matematika siswa dari skor rerata 4,34 dalam kategori “sangat tinggi” pada siklus I menjadi skor rerata 4,44 dalam kategori “sangat tinggi” pada siklus II. Model Problem Based Learning dan permainan Plucking Star dapat meningkatkan kemampuan pemecahan masalah matematika siswa dari rerata 84,7 dengan ketuntasan klasikal 81,5% pada siklus I menjadi 88,9 dengan ketuntasan klasikal 85,2% pada siklus II.